2022
DOI: 10.1002/app.53159
|View full text |Cite
|
Sign up to set email alerts
|

Excellent toughness of rigid polyvinylchloride at low temperature improved by polycarbonate‐polydimethylsiloxane block copolymer

Abstract: Rigid polyvinylchloride (PVC) is widely used in various fields, but its low impact strength at low temperature limits its deep application in some cold regions. This work utilizes polycarbonate‐polydimethylsiloxane block copolymer (PC‐b‐PDMS) to toughen PVC. PDMS segment has extremely low glass transition temperature (−126°C) and PC segment has a good compatibility with PVC, which proved by the Fourier transform infrared and dynamic mechanical thermal results. For verifying toughening effect of PC‐b‐PDMS, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…It can be found that the value of E a is decreased from 109.6 kJ/mol of pure PC to 62.7, 64.6, 59.2, and 60.5 kJ/mol, indicating the enhancement of shear dependence of blends. 59 The reduced E a broadens the processing temperature window of the blends.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…It can be found that the value of E a is decreased from 109.6 kJ/mol of pure PC to 62.7, 64.6, 59.2, and 60.5 kJ/mol, indicating the enhancement of shear dependence of blends. 59 The reduced E a broadens the processing temperature window of the blends.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The main mechanical property of the PC thermoplastics is their resistance to fracture and impact [29]. PC materials are considered environmentally friendly materials which are suitable for 3D printing [20].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, the effect of polycarbonate‐polydimethylsiloxane block copolymer (PC‐ b ‐PDMS) dosage on the toughening effect of PVC at different temperatures was investigated 14 . It was found that even at −30°C, PC‐ b ‐PDMS also had a good toughening effect on PVC when 20 phr PC‐ b ‐PDMS was added.…”
Section: Introductionmentioning
confidence: 99%